Nanocrystalline structure formation under severe plastic deformation and its influence on mechanical properties - Podrezov, Yu.M. (Физика и техника высоких давлений, 2005)
Consideration is given to the distinction between nanocrystal strengthening and Hall−Petch grain size strengthening which varies linearly with d−1/2. The important role of grain boundary structure in the strengthening formation of nanomaterials is emphasized. Static and dynamic recoveries are the main reasons limiting the minimal size of structural elements under deformation in high-deformed materials. Structural relaxation proceeding by the recovery mechanism during both the plastic deformation and unloading causes loss of strengthening in high-deformed materials. At the initial stage of repeated deformation the recovered cell structure interacts with moving dislocations in a special way. In the microdeformation level the hardening stress is practically independent of previous deformation degrees in a wide interval of deformation. The usual increase of strengthening with rise of deformation is observed only from the yield point.